Inclusive FinTech, open banking, and bank performance: evidence from China - Zhuang Liu; Xingyi Li; Zhongfei Li (Financial Innovation)
Abstract Open banking is an emerging business model that is representative of FinTech. To explore whether inclusive FinTech can improve bank performance and identify the underlying mechanisms by which this occurs, we investigate a sample of Chinese commercial banks involved in open banking during 2011–2020. The results show that inclusive FinTech can improve bank performance by improving the bank’s lending rate and liability structure, and that this positive effect is more pronounced in national and rural banks. The results indicate that inclusive FinTech has the greatest impact among banks serving the largest population and those who are excluded from the traditional financial system, and that financial inclusion does not detract from bank performance. However, the results do not provide evidence that inclusive FinTech improves bank performance by reducing risk-taking, suggesting a greater need for inclusive FinTech to focus on risk management. This study adds empirical evidence regarding the role of inclusive FinTech in banks. To promote inclusive FinTech and bank performance, developing economies like China should strengthen digital financial innovations, focus on risk management, and promote cooperation under the open finance framework.